Polylactam coated separator membrane and related coating formulation for lithium ion secondary battery
Polylactam ceramic coatings for lithium-ion battery separators address the issue of high thermal shrinkage, improving safety and performance by providing excellent thermal stability and reduced heat shrinkage.
Patent Information
- Application Number
- JP2025009668
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2015-01-05
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-23
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lithium-ion battery separators face challenges with high thermal shrinkage, which can lead to safety issues such as short circuits, especially in high-energy applications like electric vehicles.
The development of polylactam ceramic coatings for microporous battery separators, using a polylactam polymer binder combined with inorganic particles in an aqueous medium, which provides excellent thermal stability, adhesion, and reduced heat shrinkage.
The polylactam ceramic coatings achieve significant reductions in thermal shrinkage, maintaining dimensional integrity and oxidation stability at high temperatures, thereby enhancing the safety and performance of lithium-ion batteries.
Smart Images

Figure 2025066795000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of co-pending U.S. Provisional Patent Application No. 62 / 097,199, filed December 29, 2014, and No. 62 / 099,636, filed January 5, 2015, each of which is incorporated by reference in its entirety.
[0002] The present invention is directed to lithium battery separators, coated separators, formulations, and / or related methods. At least according to selected embodiments, aspects, or objectives, a method for making a polylactam coating and / or such polylactam formulation for a battery separator for a lithium ion secondary battery and / or application of the formulation to make a coated battery separator is provided. At least according to certain selected embodiments, aspects, or objectives, a method for making a polylactam ceramic coating and / or this polylactam formulation for a microporous battery separator for a lithium ion secondary battery and / or application of the formulation to make a coated microporous battery separator is provided. Preferred coatings of the present invention may have excellent thermal and chemical stability, excellent adhesion to microporous base substrates, membranes, and / or electrodes, improved bonding properties to ceramic particles, and improved, optimized, novel, or excellent resistance to thermal shrinkage, dimensional integrity, and / or oxidative stability when used in rechargeable lithium batteries, such as secondary lithium ion batteries. [Background technology]
[0003] High-temperature melting fully microporous separator membranes for lithium-ion batteries exist in the art. Japanese Patent Application No. 2014141638 discloses aromatic polyamide (aramid) porous membranes, which are claimed to provide heat resistance in non-aqueous secondary lithium-ion batteries. The aramid polymer binder proposed as a high-temperature coating requires a non-aqueous solvent, such as N-methylpyrrolidone (NMP), to form a coating solution. Aramid is not water-soluble. The coating process involves phase separation to form a porous coating on the membrane. In addition, aramid may need to be mixed with a polymer containing polar substituents due to the tendency of aramid to aggregate in solution and the difficulty of forming a uniform coating on the porous membrane.
[0004] US Patent Publication No. 2014 / 0141314 proposes a (meth)acrylic polymer binder with ceramic particles in an aqueous medium as a coating slurry for a polymer ceramic coating for a microporous separator membrane for lithium-ion rechargeable batteries. However, certain acrylic polymer binders tend to undergo chain scission along the main chain of the vinyl polymer in certain electrolytes in lithium-ion batteries, and therefore may not be very chemically stable polymer binders in certain applications. In addition, US Patent Publication No. 2014 / 0141314 proposes that spherical ceramic particles with fine surface irregularities may be preferred to achieve adhesion of the polymer ceramic coating layer to the porous base membrane, since the (meth)acrylic polymer binder / ceramic coating has adhesion between the ceramic particles and the binder in the coating layer, and in addition, to prevent the ceramic particles from peeling off when handling the membrane.
[0005] US Patent Publication No. 2011 / 0229768 discloses a method for modifying a microporous separator membrane for use in a polymer ceramic coating for a microporous separator membrane for a lithium-ion rechargeable battery. The method uses a polymer binder prepared by polymerization of a mixture of several hydrophilic and hydrophobic monomers in various monomer ratios and combinations. The colloidal coating slurry requires a plasticizer, polyethylene wax powder and surface-treated ceramic particles to prepare a stable emulsion coating slurry. The purpose of applying the coating slurry onto the microporous separator membrane is to improve the dimensional integrity of the microporous separator membrane and reduce the shrinkage of the microporous separator membrane at high temperatures, which may allow contact between the anode and cathode that would cause a short circuit in the battery. However, the coating example of US Patent Publication No. 2011 / 0229768 only achieved 18-24% thermal shrinkage at 150°C, which may not be a sufficient level of reduction in thermal shrinkage to provide the necessary level of safety required at high temperatures in certain high energy rechargeable lithium ion batteries. Summary of the Invention [Problem to be solved by the invention]
[0006] Ceramic coated composite separator membranes with low or zero thermal shrinkage would be highly desirable for use in lithium ion batteries, especially for electric vehicles and high energy and power applications. Safety is a top priority for secondary lithium ion batteries. [Means for solving the problem]
[0007] Thus, a need exists for new or improved coating formulations that not only provide a clean, environmentally friendly coating process using water or mixtures of water as the solvent in the coating slurry, at least for certain applications, but also use polymer binders that have high thermal stability against extended high temperature shutdown, reduced thermal shrinkage with improved and / or excellent dimensional integrity, and / or oxidative stability when used in lithium batteries, such as high energy rechargeable lithium ion batteries. Effect of the Invention
[0008] Depending on at least selected embodiments, aspects or objectives, the present invention may address the above needs and / or provide a clean, environmentally friendly coating process using water or a mixture of water as the solvent in the coating slurry, as well as provide new or improved coating formulations using polymer binders with high thermal stability against extended high temperature shutdown, reduced thermal shrinkage with improved and / or superior dimensional integrity, and / or oxidative stability when used in lithium batteries, such as high energy rechargeable lithium ion batteries.
[0009] Depending on at least selected embodiments, aspects or objectives, the present invention is directed to lithium battery separators, coated separators, coating formulations, and / or related methods, polylactam coatings, polylactam ceramic coatings for microporous battery separators for lithium ion secondary batteries, and / or methods of making the formulations and / or applications of the formulations to make coated microporous battery separators, the coatings of the present invention having excellent thermal and / or chemical stability, excellent adhesion to microporous base substrates, membranes, and / or electrodes, improved bonding properties to ceramic particles, and / or improved, optimized, novel and / or excellent resistance to thermal shrinkage, and / or dimensional integrity and / or oxidative stability when used in rechargeable lithium batteries, such as secondary lithium ion batteries.
[0010] According to at least certain embodiments, the composite microporous membrane and / or separator of the present invention comprises a coating composed of a polylactam polymer binder combined with inorganic particles in an aqueous medium, which is formed on at least one layer and / or one side of a microporous polyolefin separator membrane for use as a battery separator in a lithium-ion secondary battery. The preferred coating of the present invention may have increased thermal stability at high temperatures due to the high heat resistant cyclic amide chemical structure of the lactam. Polylactam polymers (particularly preferred examples include one or more polyvinylpyrrolidone (PVP) polymers) are novel binder polymers for polymer / ceramic coatings of polyolefin membranes for lithium-ion batteries when compared to other binder polymers known in the art, such as polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyvinyl acetate (PVAc) and carboxymethyl cellulose (CMC). The polylactam polymer binder has a higher decomposition temperature than PVA, PAA, PVAc and CMC. Thus, PVP is a more thermally stable polymer that, when combined with ceramic particles in aqueous media, may provide an improved high temperature coating for microporous separator membranes for lithium ion rechargeable batteries.
[0011] In addition, when applied to one or more sides or surfaces of a microporous separator membrane, the polylactam ceramic coating of the present invention can provide reduced thermal shrinkage in the machine direction and / or transverse direction under various conditions, by way of example only, at up to 150°C or higher for up to one hour or more. The lower thermal shrinkage of the microporous separator membrane can be considered an important performance characteristic, since the reduced dimensional shrinkage in the machine direction and / or transverse direction reduces the possibility of physical contact between the cathode and anode during repeated battery cycling, improving temperature-related safety performance when used as a separator membrane in a rechargeable lithium-ion battery. A ceramic-coated composite separator with either low or zero thermal shrinkage can be highly desirable for use in lithium-ion batteries, especially for electric vehicles and high energy and power applications. Safety is a top priority for secondary lithium-ion batteries.
[0012] Additionally, PVP can have good oxidative stability with little or no discoloration in the organic electrolytes typically used in lithium ion batteries, and / or can provide stability to PVP-rich ceramic coated separator membranes in the harsh environment of certain electrolytes used in certain lithium ion batteries. [Brief description of the drawings]
[0013] [Figure 1a] Cyclic voltammetry test results of poly(vinylpyrrolidone-co-vinyl acetate (Poly(VP-co-VAc)) copolymer after chemical stability test in hot (60° C.) electrolyte for 5 days. [Figure 1b] Photograph of poly(vinylpyrrolidone-co-vinyl acetate (poly(VP-co-VAc)) copolymer after chemical stability testing in hot (60° C.) electrolyte for 5 days. [Figure 2a] Cyclic voltammetry test results of polyacrylidone polymer after chemical stability test in hot (60° C.) electrolyte for 5 days. [Figure 2b]Photograph of polyacrylidone polymer (a terpolymer of vinylpyrrolidone, acrylic acid, and lauryl methacrylate) after chemical stability testing in hot (60° C.) electrolyte for 5 days. [Figure 3a] Cyclic voltammetry test results of polyvinylpyrrolidone (PVP) polymer after chemical stability test in hot (60° C.) electrolyte for 5 days. [Figure 3b] Photograph of polyvinylpyrrolidone (PVP) polymer after chemical stability testing in hot (60° C.) electrolyte for 5 days. [Figure 4] 1 is a thermogravimetric analysis (TGA) thermogram of selected polymer binders. [Diagram 5] Photographs of PVP polymers in aqueous and electrolyte media with molecular weights of 40,000, 360,000 and 1,000,000, showing various dissolution rates and gelling performance. [Figure 6] The proposed adhesion mechanism of Al2O3 ceramic particles improved by PVP coating on the separator membrane is presented. [Figure 7] Includes (a) a photograph of CE1, an uncoated PP / PE / PP tri-layer microporous separator membrane; (b) a photograph of the PVP / Al2O3 coated PP / PE / PP tri-layer microporous separator membrane sample of Example 1 that was heat shrink tested after being placed in an oven at 150°C for 10 minutes; and (c) a photograph of CE1, an uncoated PP / PE / PP tri-layer microporous separator membrane, after being placed in an oven at 150°C for 10 minutes. [Figure 8] A series of photographs of (a) polyvinyl acetate (PVAc), (b) carboxymethyl cellulose (CMC), (c) poly(vinylpyrrolidone-co-vinyl acetate) (poly(VP-co-VAc) and (d) polyvinylpyrrolidone (PVP) samples after electrolyte stability testing in hot (60 °C) electrolyte for 5 days are included. [Figure 9] a-b, containing cyclic voltammetry (CV) test results for Examples 1 and CE1, and Examples 11 and CE1, respectively. [Figure 10] 1 is a hot electrical resistance plot of Example 1, Example 4, and Example 12, where the electrical resistance in ohms-cm2 is plotted as a function of temperature (° C.). [Figure 11] 1 includes dielectric breakdown data for Example 1 and Example 12. [Figure 12] 1 includes battery cycle life test results for Example 1 compared to CE1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] According to at least certain embodiments, a preferred composite microporous membrane of the present invention comprises a coating comprised of a polylactam polymer binder in combination with inorganic particles in an aqueous medium, formed on at least one layer and / or one side of a microporous polyolefin separator membrane for use as a battery separator in a lithium battery, such as a lithium ion secondary battery. The polylactam coating of the present invention is represented by chemical formula 1: [ka] chemical formula 1 (wherein R1, R2, R3, and R4 can be any alkyl or aromatic substituent, and where R5 can be any alkyl, aromatic, or fused ring.) The polylactams may have increased thermal stability at high temperatures due to the high heat resistant cyclic amide chemical structure defined as: Preferred polylactams may be homopolymers or copolymers, and in the case of copolymers, the copolymer "X" group may be derived from vinyl, alkyl vinyl, vinyl alcohol, vinyl acetate, substituted alkyl vinyl, acrylic acid, alkyl acrylic acid, acrylonitrile, maleic anhydride, maleimide, styrene, polyvinylpyrrolidone (PVP), polyvinylvalerolactam, polyvinylcaprolactam (PVCap), polyamide, or polyimide.
[0015] In addition, "m" may have a value from 1 to 10, for example, optionally, a value from 2 to 4. Furthermore, the ratio of "l" to "n" in Chemical Formula 1 may be such that 0≦l / n≦10, optionally, 0≦l / n≦1.
[0016] Preferred examples of such polylactams include polyvinylpyrrolidone (PVP), shown in Formula 2(a) immediately below on the left (wherein m=2), and polyvinylcaprolactam (PVCap), shown in Formula 2(b) immediately below on the right (wherein m=4). [ka] chemical formula 2 (a) (b)
[0017] Of course, these preferred polylactams may be homopolymers or copolymers having various "X" copolymer groups, as described above, with such "X" copolymer groups repeated "l" times.
[0018] The performance advantages of cyclic polylactams are high thermal stability, good chemical stability, and / or reduced entropy penalty. The cyclic rings can contain up to seven elements (such as in a caprolactam ring), but if the total number of elements in the ring structure is eight or more, the polymer can operate in an acyclic manner. The chemical structure of polyvinyllactams takes advantage of the thermal stability of the amide "-NC=0" functional group present in cyclic polyaramid and polyimide (PI) structures. Polylactams can have excellent thermal and chemical stability due to the cyclic amide functionality attached to the vinyl backbone. Furthermore, polyvinyllactams can avoid the performance limitations of acrylic vinyl polymers, which can have peripheral chemical and thermal stability, because they tend to open up the vinyl backbone of the polymer when decomposed.
[0019] [ka] Polylactams can mimic the acyclic structural arrangement of carbon, hydrogen and oxygen atoms in PVAc, but polylactams are cyclic amide polymers. For example, the polylactam polyvinylpyrrolidone (PVP) can mimic the chemical structural arrangement of polyvinyl acetate (PVAc) shown in the diagram below, where a portion of each polymer is outlined by a hand-drawn curved line. [ka]
[0020] The outlined segments in each polymer can be superimposed due to the bond angles of their similar structures. The improvement in thermal stability of PVP over PVAc can be attributed to the cyclic amide containing ring characteristic of polylactams, which may explain the high temperature stability of polylactams.
[0021] Non-limiting examples of polylactam copolymers include those represented by the following formula 3: [ka] chemical formula 3 Poly(vinylpyrrolidone-co-vinyl acetate) (Poly(VP-co-VAc) shown in Chemical formula 4: [ka] chemical formula 4 and poly(vinylpyrrolidone-co-vinylcaprolactam) (poly(VP-co-VCap)) shown in [ka] chemical formula 5 The acrylate polymer may be an acrylidone polymer as shown in
[0022] Non-limiting examples of copolymers of polyvinylpyrrolidone, specifically poly(vinylpyrrolidone-co-vinyl acetate) and acrylidone, were tested for chemical stability in hot EC:EMC non-aqueous electrolyte at 60° C. for 5 days. The chemical stability results for poly(VP-co-VAc) and acrylidone are shown in FIG. 1(b) and FIG. 2(b), respectively, and can be compared to the chemical stability test results for homopolymer PVP shown in FIG. 3(b). Certain polylactam copolymers in FIG. 1 and FIG. 2 showed some discoloration in EC:EMC non-aqueous electrolyte at 60° C. for 5 days, while homopolymer PVP showed no discoloration. However, by varying the ratio of “X” copolymer groups to vinylpyrrolidone units, changing the molecular weight of the PVP and / or copolymer, and making other modifications, such discoloration may not occur.
[0023] In addition, cyclic voltammetry tests were performed on chemical stability test samples of poly(VP-co-VAc), acrylidone, and PVP, with the results shown in Figures 1(a), 2(a), and 3(a), respectively. Both poly(VP-co-VAc) and acrylidone were found to be less stable than homopolymer PVP, indicating that poly(VP-co-VAc) and / or acrylidone may undergo one or more oxidation reactions that generate one or more conductive species that cause the current levels to increase at high voltages. However, as discussed above, by changing the ratio of "X" copolymer groups to vinylpyrrolidone units, varying the molecular weight of the PVP and / or copolymer, and making other modifications, such oxidation reactions may not occur and the results may be closer to those shown in Figure 3(a).
[0024] PVP has a thermal decomposition temperature (T d) and a glass transition temperature above 170° C., making it a highly heat stable polymer. FIG. 4 shows the decomposition temperature (T) of polyvinylpyrrolidone (PVP) compared with other polymeric binders known in the prior art as polymeric binders for battery separator membrane coatings, such as polyvinyl alcohol (PVA), polyacrylic acid (PAA) and carboxymethyl cellulose (CMC). d ). The order of decomposition temperatures is PVP>PVA>CMC>PAA, indicating the higher thermal stability of polylactams when compared to PVA, CMC and PAA. In addition, the decomposition temperature of the copolymer poly(vinylpyrrolidone-co-vinylcaprolactam) (poly(VP-co-VCap) shown in the TMA thermograms in Figure 4 is lower than that of the homopolymer PVP. The initial slight loss in weight of the PVP homopolymer below 100 °C may be due to the evaporation of water or moisture present in the polyvinylpyrrolidone polymer.
[0025] A further peculiar feature of polylactams may be their tendency to associate with water due to their ability to act as H-bond acceptors. Most cyclic polyaramid polymers may be water insoluble and may require the use of organic solvents such as N-methylpyrrolidone (NMP) for dissolution. The solubility of polylactam PVP may depend on its molecular weight. For example, the higher the molecular weight of PVP, the lower the solubility rate of the PVP polymer in water. Figure 5 presents photographs of PVP polymers with molecular weights of 40,000, 360,000 and 1,000,000 in various electrolyte and aqueous media. PVP polymers with molecular weights of 40,000, 360,000 and 1,000,000 are soluble in water, but lower molecular weight PVP may dissolve faster. In addition, PVP having a molecular weight of 360,000 may form a gel when placed in a typical lithium ion battery electrolyte at 60° C. for 24 hours, while PVP having a molecular weight of 1,000,000 or more may form a solid when placed in a typical lithium ion battery electrolyte at 60° C. for 24 hours.
[0026] The coating of the present invention may be comprised of a polylactam polymer or polylactam copolymer combined with inorganic particles in an aqueous medium, formed on at least one layer and / or surface of a microporous polyolefin separator membrane for use as a battery separator in a lithium ion secondary battery. In the coating system of the present invention, the polylactam polymer or polylactam copolymer may act as a binder polymer that may act both to adhere the ceramic particles and to adhere the coating to the base separator membrane and / or electrode(s) in a lithium ion battery. Figure 6 proposes a mechanism for improved adhesion of aluminum oxide (Al2O3) ceramic particles by a PVP coating, which is one polylactam polymer coating on a microporous separator membrane. The PVP polymer has a dual function, or is bifunctional. Specifically, of the two PVP functional groups, the more hydrophilic functional group of the polymer coating may interact with the ceramic particles and act to anchor the Al2O3 molecules to the coated microporous separator membrane, while the polyolefin-based chain portion of the PVP polymer coating (the less hydrophilic portion) interacts sufficiently with the polyolefin microporous separator membrane to provide superior bonding and chemical bonding of the PVP to the Al2O3 ceramic particle component contained in the coating mixture. The result is a polymer binder coating containing Al2O3 ceramic particles that is not likely to delaminate the coated separator membrane during handling, during battery construction, and / or repeated cycling / life / use of the battery.
[0027] The particles used herein for coating can be organic and / or inorganic, preferably inorganic, and in many embodiments, ceramic particles. Non-limiting examples of inorganic ceramic particles can include silicon oxide (SiO2), aluminum oxide (Al2O3), boehmite (Al(O)OH), zirconium oxide, titanium dioxide (TiO2), barium sulfate (BaSO4), transition metal oxides, and the like or mixtures thereof. A preferred inorganic ceramic particle can be aluminum oxide. These particles can have an average particle size ranging from 0.05 to 5 μm in diameter, more preferably 0.02 to 4 μm in diameter, and most preferably 0.01 to 2 μm in diameter. For example, the coating of the present invention can be comprised of a polylactam polymer or polylactam copolymer in combination with inorganic particles, organic particles, mixtures of both, or no particles in an aqueous medium formed on at least one layer and / or surface of a microporous polyolefin separator membrane for use as a lithium ion secondary battery separator or coated battery separator membrane or layer in a battery.
[0028] The coating of the present invention containing polylactam polymer or polylactam copolymer can provide improved thermal stability at high temperatures when applied to microporous polyolefin separator membranes for use as battery separators due to its high heat resistant cyclic amide type structure. The thermal properties of uncoated polyolefin membranes can depend on the type of polyolefin, with polypropylene typically melting at about 165°C and polyethylene typically melting at about 135°C. The melting temperature of polylactams is higher than that of PP and / or PE, and when polylactams are used to coat microporous polyolefin separator membranes, the polylactam coating can reduce the thermal shrinkage of the coated microporous separator membrane.
[0029] Figure 7(b) is a photograph of a polyvinylpyrrolidone (PVP)-ceramic coated separator membrane, specifically a PP / PE / PP tri-layer microporous separator membrane coated with polyvinylpyrrolidone and aluminum oxide (PVP-Al2O3), that was heat shrink tested by placing it in an oven at 150°C for 10 minutes. Figure 7(a) is a photograph of an uncoated CE1 base membrane (PP / PE / PP tri-layer microporous base separator membrane) before placing it in an oven at 150°C for 10 minutes. Figure 7(c) is a photograph of an uncoated CE1 base membrane after placing it in an oven at 150°C for 10 minutes.
[0030] The solid lines in FIG. 7(c) represent the original dimensions of the test sample, and the horizontal dotted lines indicate the edges of the sample after shrinkage. The thermal shrinkage was measured in the machine direction (MD) and can be expressed as %MD shrinkage. The PVP-Al2O3 coated PP / PE / PP tri-layer microporous separator membrane shown in FIG. 7(b) has a machine direction (MD) thermal shrinkage of 3%, which can be considered a very low value. In contrast, the uncoated PP / PE / PP tri-layer microporous separator membrane before oven treatment shown in FIG. 7(a) has a much higher shrinkage after being placed in an oven at 150° C. for 10 minutes, as shown in FIG. 7(c). The lower thermal shrinkage of the microporous separator membrane may be a critical separator membrane performance characteristic, since the reduction in the dimensional shrinkage in the machine and transverse directions reduces the chance of physical contact between the cathode and anode during repeated battery cycling, which may lead to improved temperature-related safety performance when used as a separator membrane in a rechargeable lithium-ion battery.
[0031] The polylactam ceramic-based coating of the present invention may include one or more additives to improve the wettability of the ceramic coating slurry on the polyolefin microporous separator membrane as well as the hydration of the overall coating separator, and the base membrane may include, but is not limited to, polypropylene (PP) and / or polyethylene (PE). Such polyolefin microporous separator membranes are available from Celgard, LLC, Charlotte, North Carolina. The microporous base membrane may be manufactured, for example, by the dry stretching process (known as the Celgard® dry stretching process) of Celgard, LLC, Charlotte, North Carolina, or by a wet process, sometimes also known as the phase separation or extraction process of Celgard Korea Co., Ltd., South Korea, Asahi Kasei Co., Japan, and / or Tonen Co., Japan, or may be a non-woven type membrane. The base film can be a single layer (one or more plies) of polypropylene and / or polyethylene, or a multi-layer film such as a three-layer film, e.g., polypropylene / polyethylene / polypropylene (PP / PE / PP) or polyethylene / polypropylene / polyethylene (PE / PP / PE), or a bi-layer film (PP / PE, PE / PP, PE / PE, PP / PP).
[0032] A specific isotactic polypropylene has a surface energy of 30.1 mN / m at 20° C., which is lower than the specific linear polyethylene surface energy of 35.7 mN / m. In order to completely and quickly wet the base PP and / or PE microporous separator membrane during the coating process, the coating slurry should have a similar surface energy to the base PP and / or PE microporous separator membrane. The polylactam ceramic-based coating of the present invention may contain one or more additives to enable more rapid wetting of the ceramic slurry coating on the microporous separator, such as polypropylene, polyethylene, or PP / PE / PP, and such additives may also help improve the overall hydration of the final coated separator when used in a battery in an electrolyte.
[0033] The coating of the present invention may use polyvinyl alcohol (PVA) as an additive component to achieve rapid wetting of the PVP polymer-ceramic slurry on the PP microporous separator membrane or on the PP surface of the PP / PE / PP tri-layer microporous separator membrane, and to achieve improved hydration of the final coated separator inside the electrolyte-filled battery. For the purpose of this description, the PP microporous separator membrane is understood to mean both the PP microporous membrane, the PP / PE / PP tri-layer microporous membrane, or the multi-layer microporous membrane containing PP and PE. It has been found that the amount of the PVA additive component can be important. If the PVA additive component is too small, the PP microporous separator membrane fails to wet or cannot be highly hydrated with the electrolyte in the battery. In addition, a low amount of the PVA additive component in the PVP coating may result in higher thermal shrinkage of the PVP ceramic coated PP microporous separator. In contrast, an amount of PVA in the PVP coating higher than the optimal range may result in discoloration of the coated PP microporous separator membrane in the typical non-aqueous electrolyte(s) used in lithium ion batteries. In addition, a higher amount of PVA in the PVP coating may result in gassing at higher voltages and lower oxidative stability as measured by cyclic voltammetry (CV). It has been found that the PVP binder has good oxidative stability in the electrolyte with little discoloration of the electrolyte, and further, it has been found that wetting additives such as PVA can enable the PVP-ceramic coating to have a high wetting rate on the PP-based microporous membrane, improving the overall hydration of the final coated separator. In some cases, the ratio of PVP:PVA in the polymer ceramic coating may be 10:0.1 to 10:10.
[0034] Working Example The lactam-based polymer ceramic coating of the present invention may have improved resistance to high temperature stability and thermal shrinkage without adversely affecting battery separator performance properties such as Gurley, wetting (or hydration) and electrolyte stability. Gurley (JIS P 8117) is defined as the time (in seconds) required for 100 cc of air to pass through 1 square inch of porous material at a constant pressure of 4.8 inches of water. Wetting performance is determined by placing a drop of electrolyte on the surface of the porous membrane and measuring the wetting time. Electrolyte stability of the polymer is measured by placing a sample in an electrolyte such as, but not limited to, EC:EMC with 1 mole of LiPF6, heating the sample to 60°C and observing the color change. Subsequent columbic and / or cyclic voltammetry measurements of the stability test sample indicate whether the polymer sample undergoes an oxidation reaction that may generate one or more conductive species, thereby increasing the current level.
[0035] Extensive research was conducted in the development of the membranes of the present invention to determine preferred formulation compositions in terms of homopolymer and / or copolymer content, preferred ratios of polylactam to ceramic particles, and preferred methods for improving the hydration of polylactam-based ceramic coating slurries onto polyolefin separator membranes, and ultimately improving the hydration of the coated separator when used in the electrolyte inside a battery, such as a secondary lithium ion battery.
[0036] The effect of polyvinyl alcohol (PVA) as an added component in the PVP-ceramic coating on separator properties such as resistance to Gurley, wetting, electrolyte stability and thermal shrinkage is demonstrated in the examples set forth in Tables 1 and 2 below, in which the PVP:PVA ratio is varied, specific copolymers of PVP are used (see, e.g., Examples 7 and 8), and specific differences in the amount of ceramic particles in the coating are achieved.
[0037] [Table 1] [Table 2] 〇=Excellent △=minimum limit × = Poor or unacceptable
[0038] For PVP:PVA ratios such as 1:0.1, 1:0.2, 1:0.01, and 1:0, the Gurley remained fairly unchanged at 450-500 sec / 100cc (see Examples 1-4, and 9-10), but increased by about 30% at a PVP:PVA ratio of 1:0.5 (see Example 5), and by about 44% at a PVP:PVA ratio of 1:1 (see Example 11). Comparing the 442 sec / 100cc Gurley for the uncoated base separator membrane CE1 with Example 4, where the PVP:PVA ratio is 1:0.2, demonstrates that PVP:PVA ratios in the ceramic coating at PVA additive levels of 0.2 or less (compared to 1 part PVP) do not adversely affect the Gurley.
[0039] Excellent wetting of the membrane was observed at PVP:PVA ratios such as 1:0.1, 1:0.2, and 1:0.5, demonstrating that improved wetting can be achieved by adding small amounts of hydrophilic additives.
[0040] The electrolyte stability was good at PVP:PVA ratios of 1:0, 1:0.01, 1:0.1, and 1:0.2, but only slightly tolerant at PVP:PVA ratios such as 1:0.5 and 1:1, indicating that too high an amount of PVA may result in undesirable oxidation of the coating samples in the electrolyte.
[0041] Heat shrinkage at 150°C for 10 minutes was observed to be 25% in the machine direction (MD) and 3% in the transverse direction (TD) in the absence of non-PVA additive components (see Example 9). A significant reduction in heat shrinkage was achieved with the addition of the PVA additive as shown for various inventive examples such as Examples 1-8 and 10-12 (see, for example, Example 1 where the MD shrinkage was reduced to 3% and the TD shrinkage was reduced to 2%).
[0042] A PVP:PVA ratio of 1:0.1 was found to be in the preferred PVP:PVA blend ratio range, and no oxidation or discoloration was observed in the electrolyte stability test.
[0043] The effect of the amount of aluminum oxide (Al2O3) in the ratio of PVP:Al2O3 on the separator properties of resistance to Gurley, wetting, electrolyte stability and thermal shrinkage is demonstrated in the examples given in Tables 1 and 2 where the PVP:Al2O3 ratio is varied in different amounts.
[0044] The effect of copolymer poly(vinylpyrrolidone-vinyl acetate) (poly(VP-co-VAc)) and copolymer poly(vinylpyrrolidone-vinylcaprolactam) (poly(VP-co-VCap)) on the separator properties of resistance to Gurley, wetting, electrolyte stability and thermal shrinkage is demonstrated in Example 8 where copolymer poly(VP-co-VAc) is used in a copolymer:PVA ratio of 1:0.1 (PVA is an additive that helps improve separator hydration) and Example 7 where copolymer poly(VP-co-VCap) is used in a copolymer:PVA ratio of 1:0.1. For comparison, Example 1 provides an example of a PVP homopolymer without a copolymer component at the same polymer:PVA ratio of 1:0.1 and the same ceramic:binder ratio of 95:5.
[0045] The Gurley for both copolymer examples, Example 7 and Example 8, is 504 and 510 sec / 100 cc, respectively, indicating good permeability.
[0046] As expected due to the hydrophilicity of the copolymers, excellent wetting of the coated polyolefin microporous membranes of Examples 7 and 8 is observed.
[0047] The electrolyte stability of poly(vinylpyrrolidone-vinylcaprolactam) of Example 7 is marginal, while the electrolyte stability of poly(vinylpyrrolidone-vinyl acetate) of Example 8 is unacceptable or poor. The results of exposure of selected homopolymer and copolymer binders to electrolyte at 60° C. during stability testing are shown in FIGS. 1(b), 2(b) and 3(b). FIG. 3(b) shows that the PVP homopolymer remains colorless or substantially colorless, while poly(VP-co-VAc) shown in FIG. 1(b) becomes discolored and dark. Columbium and / or cyclic voltammetry (CV) oxidation analysis data for poly(VP-co-VAc) shown in FIG. 1(a) demonstrates that poly(VP-co-VAc) is less stable than PVP and indicates that poly(VP-co-VAc) can undergo oxidation reactions that generate conductive species that increase current levels at high voltages. However, as discussed above, by varying the ratio of "X" copolymer groups to vinylpyrrolidone units, varying the molecular weight of the PVP and / or copolymer, among other modifications, such discoloration is unlikely to occur and can be controlled or reduced.
[0048] The heat shrinkage at 150°C for 10 minutes for Examples 7 and 8 is higher in MD (but the same in TD), indicating that the homopolymer PVP coating formulation of Example 1 may be preferred in certain cases in terms of reduced heat shrinkage.
[0049] The effect of different known polymer binders such as carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyethylene oxide (PEO) on the separator properties of resistance to Gurley, wetting, electrolyte stability and thermal shrinkage are demonstrated in CE2, CE3 and CE4, respectively.
[0050] The Gurleys for CMC, PVA, and PEO were all comparable and in the range of 450-500 sec / 100 cc, indicating that these binders in combination with ceramic had good permeability, e.g., comparable to Example 1 of the present invention.
[0051] Ceramic coatings containing known binders PEO and CMC (see CE4 and CE2) had little or poor wetting of the membrane, whereas ceramic coatings containing known binder PVA had good wetting comparable to, for example, inventive Example 1.
[0052] The electrolyte stability of CE4 (with known binder PEO) is good (e.g., comparable to inventive Example 1), whereas the electrolyte stability of CMC and PVA (CE2 and CE3) was marginal or poor or unacceptable.
[0053] Looking more deeply at electrolyte stability, Figure 8 shows photographs of samples of PVAc, CMC, poly(VP-co-VAc) and PVP after electrolyte stability testing in hot (60°C) electrolyte (herein, EC:EMC with 1 molar LiPF6 electrolyte) for 5 days. It should be noted that discoloration is observed in all polymer binders except PVP, but the copolymer shown in Figure 8(c) may be modified to reduce such discoloration.
[0054] Cyclic voltammetry (CV) plots are included in Figure 9. In Figure 9(a), the oxidation analysis of the PVP-rich coating formulation of the coated membrane of Example 1 (the coating contains a PVP homopolymer with a PVP:PVA ratio of 1:0.1) is compared with the uncoated base membrane CE1, both behave very similarly in the electrolyte. In Figure 9(b), the oxidation analysis of the PVA-rich coating formulation for the coated membrane of Example 11 (the coating contains a PVP homopolymer with a PVP:PVA ratio of 1:1) is compared with the uncoated base membrane CE1. The PVP-rich formulation outperforms the PVA-rich formulation in this case in terms of oxidation stability.
[0055] The optimum range of molecular weight of PVP is in the molecular weight range of 200,000 to 3,500,000, more preferably in the molecular weight range of 300,000 to 3,000,000, and most preferably in the molecular weight range of 300,000 to 2,000,000 g / mol. At a molecular weight below 100,000, PVP may dissolve in the hot (60° C.) electrolyte, which may not allow the coating to adhere to the base microporous membrane, thus negatively affecting the battery performance.
[0056] The separator performance properties of two exemplary formulations of PVP:Al2O3 from Example 1 and Example 12 coated onto the PP / PE / PP tri-layer microporous separator membrane are shown in Table 3.
[0057] [Table 3]
[0058] CE1 and CE5 are uncoated 3-layer PP / PE / PP microporous separator membranes with thicknesses of 16 μm and 14 μm, respectively. The pin puncture strengths of uncoated CE1 and CE5 are 298 and 314 gf, respectively. The coating data provided in Table 3 shows that the pin puncture strengths of the 4 μm coated samples, Example 1 and Example 12, are essentially unchanged, indicating that the coating may not adversely affect the strength of the separator membrane. There is a significant improvement in the heat shrinkage of the coated separators, Example 1 and Example 12. At 130° C., both Example 1 and Example 12 showed low % MD / TD heat shrinkage values of 1.4 / 0.4 and 1.8 / 0.3. At a very high heat shrinkage temperature of 150° C., the % MD / TD heat shrinkage at 10 minutes is 3 / 2 for both Example 1 and Example 12, but the heat shrinkage at 150° C. for 1 hour is 5 / 2 for Example 1 and 5 / 3 for Example 12. The % thermal shrinkage values of TD shrinkage ≦3% and MD shrinkage ≦5% may predict that the coated PVP:Al2O3 PP / PE / PP separator membrane may have high thermal stability in lithium ion batteries.
[0059] The high temperature stability of the PVP:Al2O3 coating is also demonstrated in the thermal shutdown hot electrical resistance (hot ER) test results shown in Figure 10, where Example 1 and Example 12 have enhanced high temperature shutdown up to 190°C. The onset of shutdown occurs at 135°C due to the inner polyethylene layer in the PP / PE / PP tri-layer base membrane. The PVP:Al2O3 coated PP / PE / PP has both low temperature shutdown and enhanced dimensional stability up to high temperature, which may reduce the possibility of physical contact between the cathode and anode during repeated battery cycling with improved temperature-related safety performance when used as a separator membrane in rechargeable lithium ion batteries.
[0060] In addition, the PVP:Al2O3 coating of the present invention may not adversely affect the electrical resistance (ER) of the microporous separator membrane. The ER of the coated Example 1 and Example 12 is 1.99 ohm-cm, respectively. 2 and 1.57 ohm-cm 2 and it can be demonstrated that the coating of the present invention promotes good ionic conductivity.
[0061] In addition, the PVP:Al2O3 coating of the present invention may not adversely affect the dielectric breakdown (DB), also known as the HiPot test, of the microporous separator membrane. When compared to the uncoated separator membranes CE1 and CE5, the DB value increases, demonstrating that the force required to cause a short circuit in a lithium battery may be higher. Figure 11 shows the DB results of the laboratory coated samples of Example 1 and Example 12, with DB values of about 2000V. The coating of the present invention shows improved high dielectric breakdown, indicating that the strength of the separator membrane is improved by the coating.
[0062] FIG. 12 shows that the PVP:Al2O3 coating improves the cycle life of the coated separator, which can be important for long cycling life in high-energy, high-power lithium-ion batteries.
[0063] It has been found that certain preferred PVP-ceramic coating formulations include homopolymer PVP, with the added PVA being added in preferred ranges, such as the ratios detailed above.
[0064] The preferred range of Al2O3 ceramic particles in the PVP coating is in the range of 60-99 wt%, more preferably in the range of 70-99 wt%, and most preferably in the range of 80-99 wt%.
[0065] The optimum coating layer thickness may be in the range of 1 to 8 μm, more preferably in the range of 2 to 6 μm, and most preferably in the range of 2 to 4 μm.
[0066] The specific optimum PVP ceramic coating on a polyolefin microporous membrane is 1) Gurley value in the range including 500 sec / 100cc 2) Membrane Wetting: Excellent 3) Electrolyte stability: Excellent, indicating low oxidation of the binder by the electrolyte 4) MD / TD% heat shrinkage in the range of 3 / 2 inclusive at 150℃ for 10 minutes The separator may have certain preferred performance characteristics, including, but not limited to:
[0067] Test Method Thickness Thickness is measured using an Emveco Microgage 210-A precision micrometer thickness gauge according to test procedure ASTM D374. Thickness values are reported in micrometers, μm.
[0068] Puncture strength The test specimens are first preconditioned at 73.4°C and 50% relative humidity for a minimum of 20 minutes. An Instron Model 4442 is used to measure the puncture strength of the test specimens according to ASTM D3763. Thirty measurements are taken across the diagonal of a 1 1 / 4" x 40" continuous specimen and averaged. The needle has a radius of 0.5 mm. The descent rate is 25 mm / min. The film is tightly held in a clamping device that utilizes an O-ring to hold the test specimen firmly in place. The diameter of this clamping area is 25 mm. The displacement of the film penetrated by the needle (in mm) is recorded against the force (in grams of force) exerted by the test film. The maximum force is the puncture strength in grams force (gf). A load vs. displacement plot is generated by this test method.
[0069] Coating layer loading The coating layer loading is measured using ASTM D3776 and is expressed in gsm or mg / cm 2 It is expressed as:
[0070] Gurley Gurley (JIS P 8117) is defined as the time in seconds required for 100 cc of air to pass through 1 square inch of porous material at a constant pressure of 4.8 inches of water.
[0071] Electrical Resistivity (ER) (also known as Ionic Resistance, IR) The electrical resistance in ohms-cm of the separator filled with electrolyte 2 The unit of electrical resistance is ohm-cm. 2The separator resistance is characterized by cutting small pieces of separator from the finished material and placing them between two blocking electrodes. These separators are saturated with battery electrolyte having 1.0 M LiPF6 salt in EC / EMC solvent in a volume ratio of 3:7. The resistance R in ohms (Ω) of the separator is measured by a four-probe AC impedance technique. To reduce measurement errors on the electrode / separator interface, multiple measurements are required by adding more layers. The electrical (ionic) resistance Rs (Ω) of the separator saturated with electrolyte is then calculated based on the measurements of multiple layers using the formula R s =p s l / A (where P s is the ionic resistivity of the separator in Ω-cm and A is cm 2 where l is the electrode area in cm and l is the separator thickness in cm. s / A is the slope = p s The slope is calculated for the change in separator resistance (ΔR) with respect to the number of layers (Δδ) given by / A=ΔR / Δδ.
[0072] Heat shrink Shrinkage is measured by placing the coated test sample between two sheets of paper, then clipping them together to hold the sample between the papers and hanging in an oven. For the "130°C 1 hr" test, place the sample in a 130°C oven for 1 hour. For the "150°C 10 min" test, place the sample in a 150°C oven for 10 minutes. For the "150°C 1 hr" test, place the sample in a 150°C oven for 1 hour. After the specified heating time in the oven, remove each sample and tape it to a flat opposing surface using double-sided adhesive tape to flatten and smooth the sample for accurate length and width measurements. Shrinkage is measured in both the machine direction (MD) and transverse direction (TD) and is expressed as %MD shrinkage and %TD shrinkage.
[0073] Dielectric breakdown (DB) A voltage is applied to the separator membrane until dielectric breakdown of the sample is observed. A strong separator exhibits a high DB. Non-uniformity in the separator membrane may result in lower DB values.
[0074] Hot ER Hot electrical resistance is a measure of the resistance of the separator membrane as the temperature is increased linearly. An increase in resistance, measured as impedance, corresponds to a collapse in the pore structure due to melting or "shutdown" of the separator membrane. A decrease in resistance corresponds to opening of the separator due to aggregation of the polymer, a phenomenon called loss of "melt integrity." If the separator membrane maintains a high level of electrical resistance, this indicates that the separator membrane can prevent shorting of the battery electrodes.
[0075] electrolyte stability A 3-5 gram size sample (cut into small pieces if the sample is a membrane) is added to 20 ml of EC:EMC with 1 molar LiPF6 electrolyte in a covered container and then placed in a 60°C oven for 4-5 days. Observations are recorded when the sample is first placed in the container containing the electrolyte, and any changes in electrolyte color, changes in sample color, and the presence of gas evolution are recorded daily during the 4-5 day storage period.
[0076] Cyclic Voltammetry (CV) Cyclic voltammetry (CV) is performed to investigate the electrochemical stability of additive materials in 1M LiPF6 in EC:EMC, a typical lithium-ion battery electrolyte. Cyclic voltammetry is commonly used to investigate the electrochemical properties of analytes in solution. The samples are prepared as described in the electrolyte stability test, and then the samples are subjected to CV testing.
[0077] wet To test the wetting of the base membrane by the coating slurry, a dropper is used to place a drop of the coating slurry on the surface of the microporous membrane and the wetting of the membrane by the slurry is observed and recorded.
[0078] To test the wetting of a membrane of the invention coated with an electrolyte, a dropper is used to place a drop of electrolyte on the surface of the coated microporous membrane and the wetting of the membrane by the electrolyte is observed and recorded.
[0079] The present invention may be embodied in other forms without departing from its spirit or essential attributes and, accordingly, reference should be made to the appended claims, rather than the foregoing specification, as indicating the scope of the invention.
[0080] Additionally, the invention as preferably disclosed herein may be practiced in the absence of any element not specifically disclosed herein.
Claims
1. 1. A microporous battery separator membrane, comprising: one or both sides of the microporous battery separator membrane are coated with a polylactam ceramic coating composed of ceramic particles, polyvinyl alcohol (PVA), and a polylactam, the polylactam being polyvinylpyrrolidone (PVP) or polyvinylcaprolactam (PVCap); The polylactam has a molecular weight of 200,000 g / mol to 3,500,000 g / mol.
2. 10. The microporous battery separator membrane of claim 1, wherein said coating further comprises an additional polylactam defined by the general formula: 【Chemistry 1】 (In the formula, R 1 , R 2 , R 3 , and R 4 is an alkyl or aromatic substituent; R 5 is alkyl, aromatic, or fused ring, "m" has a value from 1 to 10, "n" is an integer, and "l" is an integer, with 0≦l / n≦10.
3. In the general formula, "X" is a copolymer group repeated "l" times, and the cyclic ring contains up to 7 elements (such as in a caprolactam ring); 3. The microporous battery separator membrane of claim 2, wherein the polymer behaves acyclically when the total number of elements in the cyclic structure is 8 or greater.
4. the additional polylactam is a homopolymer or a copolymer; 3. The microporous battery separator membrane of claim 2, wherein in the case of said copolymer, the copolymer "X" group is derived from vinyl, alkyl vinyl, substituted alkyl vinyl, vinyl alcohol, vinyl acetate, acrylic acid, alkyl acrylic acid, acrylonitrile, maleic anhydride, maleimide, styrene, polyvinylpyrrolidone (PVP), polyvinylvalerolactam, polyamide, or polyimide.
5. 1. A microporous battery separator membrane, comprising: the microporous battery separator membrane is coated on one or both sides with a polylactam ceramic coating; 1. A microporous battery separator membrane, wherein the polylactam of the polylactam ceramic coating is defined by the chemical structure shown in the general formula: 【Chemistry 2】 (In the formula, R 1 , R 2 , R 3 , and R 4 is an alkyl or aromatic substituent; R 5 is alkyl, aromatic, or fused ring, and "m" is a value from 1 to 10; or the polylactam has a molecular weight of 200,000 g / mol to 3,500,000 g / mol, the polylactam being polyvinylpyrrolidone (PVP) or polyvinylcaprolactam (PVCap) or a homopolymer or copolymer thereof; In the case of said copolymers, the copolymer "X" group is derived from vinyl, alkyl vinyl, substituted alkyl vinyl, vinyl alcohol, vinyl acetate, acrylic acid, alkyl acrylic acid, acrylonitrile, maleic anhydride, maleimide, styrene, polyvinylpyrrolidone (PVP), polyvinylvalerolactam, polyamide, or polyimide; A microporous battery separator membrane, wherein the polylactam ceramic coating comprises polyvinyl alcohol (PVA) added in the range of 0.1 to 90 weight percent to the polylactam.
6. 10. The microporous battery separator membrane of claim 1, wherein said additional polylactam is polyvinylpyrrolidone (PVP). 【Chemistry 3】
7. 10. The microporous battery separator membrane of claim 1, wherein the molecular weight of said polyvinylpyrrolidone (PVP) ranges from 200,000 g / mol to 3,500,000 g / mol.
8. 10. The microporous battery separator membrane of claim 1 or 5, wherein the ceramic coating slurry and solvent is water or an aqueous mixture containing a primary, secondary, or tertiary alcohol.
9. The polyvinyl alcohol is added in an amount ranging from 0.1 to 50 weight percent based on the polyvinyl caprolactam; The polyvinylcaprolactam is added in the range of 0.1 to 50 weight percent of the ceramic; and / or 10. The microporous battery separator membrane of claim 1 or 5, wherein the ceramic coating has a solids in water ratio in the range of 1 to 90 weight percent.
10. the separator membrane of the microporous base substrate is a polyolefin; and / or The microporous base substrate separator membrane is made using a dry stretching process or a wet process; or 10. The microporous battery separator membrane of claim 1 or 5, wherein the separator membrane of the microporous base substrate is a non-woven membrane.
11. the ceramic is ceramic particles; the average particle size of the ceramic particles is between 0.05 and 4 μm; and / or The thickness of said coating is less than 10 μm.
10. The microporous battery separator membrane of claim 1 or 5.
12. When heat shrunk in the machine direction at 150° C. for 1 hour, the shrinkage rate is 9% or less. When heat-shrunk in the machine direction at 150° C. for 10 minutes, the shrinkage rate is 9% or less. The shrinkage rate in the transverse direction when contracted under conditions of 150°C for 1 hour is 9% or less.
10. The microporous battery separator membrane of claim 1 or 5, wherein the shrinkage percentage when heat shrunk in the transverse direction at 150°C for 10 minutes is 9% or less.
13. 1. A method for improving adhesion of ceramic particles on a microporous separator membrane, comprising: providing a polylactam polymer coating as a binder between the ceramic particles and the microporous separator and / or providing a polylactam polymer coating as a binder between the ceramic particles; a polylactam polymer having a molecular weight of 200,000 g / mol to 3,500,000 g / mol selected from homopolymers or copolymers of polyvinylpyrrolidone (PVP) or polyvinylcaprolactam (PVCap), e.g. a bifunctional polylactam polymer having both hydrophilic and non-hydrophilic functional groups; the more hydrophilic functional group of the bifunctional group interacts with the ceramic particles and anchors the ceramic particles to the coated microporous separator, while the polyolefin-type chain portion of the less hydrophilic functional group interacts with the microporous separator. The method includes:
14. 14. The method of claim 13, wherein the polylactam ceramic base coating includes one or more additives to improve the wetting of the ceramic coating slurry onto the polyphenylene phosphate microporous separator and to improve the wetting of the entire coated separator.
15. The polylactam ceramic base coating uses polyvinyl alcohol (PVA) as an additive component to achieve rapid wetting of the PVP polymer ceramic slurry on the PP microporous separator or on the PP / PE / PP trilayer microporous separator; and Achieving improved wettability for the final coated separator in an electrolyte filled battery; The PP microporous separation membrane means a PP microporous membrane, a PP / PE / PP three-layer microporous membrane, or a multi-layer PP and PE coated microporous membrane; The method according to claim 13 or 14, wherein the ratio of PVP:PVA in the polymeric ceramic coating is from 10:0.1 to 10:10.
Citation Information
Patent Citations
Polymer li-ion battery and separator thereof
JP2013187196A
A method for manufacturing a separator, a separator manufactured by the method, and an electrochemical element equipped therewith.
JP2014534570A
Separator for non-aqueous electrolyte cell and non-aqueous electrolyte cell using same
WO2013080946A1
Freestanding, dimensionally stable microporous webs
WO2014145849A1